KONSEP DAN IMPLEMENTASI PEMBINAAN RELIGIUSITAS SISWA DI SMA - Najib, Muhammad Ainun (IAIIG Cilacap, 2018)
The promotion of religiosity among young people or youth needs to get serious attention and become a priority scale that must be realized simultaneously by all parties. The ultimate subject matter concerning religiosity among adolescents today is the blurring of moral values in the eyes of the younger generation. They are faced with various contradictions and diverse moral experiences, causing them to confuse to choose what is right and what is wrong. This is evident in adolescence. The contradictions that exist in the life of adolescents that inhibit the establishment of religiosity.The development of student relokasitas in school is essentially to realize the values of religion as a tradition of behavior that is followed by students and other school residents. To instill values in fostering student religiosity in schools can be done with several methods, among others through exemplary, habituation and advice by education in schools Keywords: coaching, religiosity, high school students, implementation